Preparation and properties of citric acid-crosslinked chitosan salt microspheres through radio frequency assisted method. (May 2023) - Zhang, Lihui; Zhang, Min; Adhikari, Benu; Zhang, Lujun
Abstract: High salt intake is one of the reasons causing dietary risk for death from noncommunicable diseases. In this study, citric acid-crosslinked chitosan (CsC) was prepared using chitosan and citric acid under radio frequency (RF) assisted method, which was considered to absorb Cl − in NaCl and further produce high-saltiness microspheres to regard as a low-sodium salt. The characterization and in vitro bioaccessibility of salt microspheres treated with RF (CsC-RF-NaCl) were investigated. The maximum Na + release capacity of CsC-RF-NaCl occurred for 3 h at 30 mm of plate spacing, pH 4 and NaCl-to-CsC-RF mass ratio of 2:1. Electrostatic attraction was responsible for the formation of CsC-RF-NaCl microparticles. CsC-RF-NaCl microparticles exhibited an irregular spherical shape, the surface of microspheres showed a more homogeneous Na + and Cl − dispersion and higher ratio of Na: Cl. CsC-RF-NaCl microparticles were excellent thermal stability, and pleasantly hygroscopic. In addition, the CsC-RF-NaCl microparticles showed the higher release of Na + during oral digestion and lower bioaccessibility in intestinal digestion. The Na + content of CsC-RF-NaCl microparticles was decreased up to 61.80% compared to NaCl at the same saltiness. Therefore, CsC-RF-NaCl microparticles were considered as a low-sodium salt for surface-salted foods. Graphical abstract: Image 1 Highlights: CsC salt microsphere was prepared by radio frequency method. CsC-RF-NaCl microparticles showed pleasantly hygroscopic and uniform shape. Surface of CsC-RF-NaCl microparticles showed a homogeneous Na + and Cl − dispersion. CsC-RF-NaCl microparticles were saltier than normal salt.